(untitled) (Global Journal of Medical Research, 2023)
Introduction Adenomyosis is a common estrogen-dependent a benign gynaecological disease characterized by endometrial glands and stroma invading implanting and proliferating within the myometrium to form diffuse or localized lesions Adenomyosis is common in women of childbearing age The signs and symptoms include dysmenorrhea menorrhagia abnormal uterine bleeding enlarged uterus dyspareunia and infertility which can seriously affect the patient s quality of life The prevalence of adenomyosis varies widely from 5 to 70 depending on the method used for diagnosis and the rate of diagnosis during hysterectomy is approximately 20 30 Aim of the study The aim of this study was to evaluate and compare the effectiveness between LNG-IUS and Dienogest among the woman with symptomatic adenomyosis